ANALISIS SUSTAINABLE COMPETITIVE ADVANTAGE FESTIVAL BANDENG SEBAGAI DAYA TARIK WISATA BUDAYA DI RAWA BELONG, JAKARTA BARAT - Teresia; Yudhiet Fajar Dewantara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Rawa Belong Bandeng Festival is an annual cultural festival rooted in the acculturation of Betawi and Chinese ethnicities, held in West Jakarta to welcome the Chinese New Year and grounded in the